Influences of malic acid and nisin supplementations on the decimal reduction times of E. coli O157 H7 in mildly-heated young coconut liquid endosperm - Estilo, Emil Emmanuel C.; Gabriel, Alonzo Alulod (Quezon City UP College of Home Economics, 2012)
This study was conducted to determine the effects of malic acid (800-1500 ppm) and nisin (0-150 ppm) supplementation on the heat resistance of E. coli O157:H7 in young coconut liquid endosperm. Determination of the maximum malic acid supplementation level through a multi-level sensory test showed that unsweetened and undiluted liquid endosperm can be added with the acid up to 1300 ppm. As for nisin, the supplementation level of 150 ppm was based on the maximum allowable amount approved by the Codex Alimentarius. The Central Composite Rotatable Design was applied to determine the various malic acid - nisin concentration combinations prior to thermal inactivation studies. The lowest D55 value was observed in the combination of 1500 ppm malic acid and 75 ppm nisin at 14.89 ± 4.17 min, while highest was 26.44 ± 9.81 min in the combination of 1397 ppm malic acid and 128 ppm nisin. The D55 values established from the combinations tested did not significantly vary. Within the operable ranges of supplementation tested, a general increase in the susceptibility of the cells towards heating was observed with increasing malic acid concentration. The opposite was observed for nisin. It was however emphasized that all supplementation combinations resulted in D55 values significantly lower than that in the unsupplemented medium, reducing the heat resistance of the cells by as much as 3 folds. therefore, thermal processes to be established in the supplemented liquid endosperm shall be less severe, and may be applied to preserve sensory attributes. The study recommended increase in malic acid supplementation with simultaneous addition of sugar to further increase lethality of the process. Slight increase in heating temperature may also result to better process schedules.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Food preservatives; Coconut products; Escherichia coli 0157:H7.